THE CAPITAL ADEQUACY RATIO MODERATED ENTERPRISE RISK MANAGEMENT ON FINANCIAL DISTRESS - Lusmeida, Herlina; Gunawan, Ezra (Jurnal Riset Bisnis dan Manajemen, 2025)
Over recent decades, digital innovations in product creation, A corporation is in financial distress when it is having trouble making ends meet.  Examining how operational, credit, liquidity, and market risk relate to financial hardship is the primary goal of this study. Also, this study aims to examine Indonesian banking businesses listed on the BEI from 2015 to 2022 to see whether the capital adequacy ratio may mitigate the effect of risk management on financial hardship.  Logistic regression analysis, performed in Stata 17.0, is the backbone of this study methodology.  Purposive sampling is used in the sampling procedure.  The findings reveal that credit risk has no effect on financial hardship, but operational risk, liquidity risk, and market risk do. The capital adequacy ratio decreases the detrimental effects of liquidity risk and market risk on financial issues, while reducing the positive effects of operational risk and credit risk, according to this study.